Prevalence and molecular identification of hypodermosis from slaughtered cattle in Sulaymaniyah province, Iraq - Mohammed, Aram A; Hama Soor, Taib A; Abdulqadir, Mardin O (The Journal of Infection in Developing Countries, 2024)
Introduction: Hypodermosis is a subcutaneous infestation in cattle that is caused by larvae of Hypoderma spp. and it is an economically important disease in the cattle industry. This study aimed to find the prevalence rate of hypodermosis and identify variations in the COX1 gene among isolates present in Sulaymaniyah, in the Kurdistan region of Iraq. Methodology: The study was conducted in a Sulaymaniyah slaughterhouse from March to July 2021. The carcasses of 867 cattle were carefully checked before and after skinning them to record the presence of boils containing the larvae of Hypoderma spp. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using TaqI enzyme, and sequencing of the COX1 gene were used for diagnosis and molecular characterization of Hypoderma spp. Results: The rate of infestation with Hypoderma bovis was 1.61% and the highest rate (3.57%) was detected in April. The disease was significantly (p < 0.05) higher in local breeds at 2.79%. PCR-RFLP confirmed that all recorded species were H. bovis. The result was further confirmed by Sanger sequencing of the COX1 gene of the isolated species. Comparison of the sequences of the conserved COX1 gene of the parasite led to identification of six different haplotypes in the research area. Two of the haplotypes were previously recorded internationally, while four new haplotypes associated with four novel mutations were recorded for the first time in the study region. Conclusions: Based on these results we can conclude that H. bovis is a widespread species in the research region.